Haemophilus influenzae serotype b seroprevalence in central Lao PDR before and after vaccine introduction. - Lisa Hefele; Jana Lai; Keoudomphone Vilivong; Toukta Bounkhoun; Valin Chanthaluanglath; Anisone Chanthongthip; Anne Balloch; Antony P Black; Judith M Hübschen; Fiona M Russell; Claude P Muller (PLoS ONE, 2022)
Introduction Vaccination has dramatically reduced invasive Haemophilus influenzae type b (Hib) disease worldwide. Hib vaccination was introduced in the Lao PDR in 2009, as part of the pentavalent vaccine. To contribute to the understanding of the epidemiology of Hib in Lao PDR and the protection levels before and after the introduction of the vaccination, we tested serum samples from existing cohorts of vaccine age-eligible children and unvaccinated adolescents for antibodies against Hib. Methods Serum samples from 296 adolescents born before vaccine introduction and from 1017 children under 5 years (vaccinated and unvaccinated) were tested for anti-Hib antibodies by ELISA. Bivariate analyses were performed to investigate factors associated with long-term protection. Results The vast majority of all participants showed evidence of short- (42.7%) or long-term (56.1%) protection against Hib. Almost all of the unvaccinated adolescents had antibody titers indicating short-term protection and almost half (45.6%) were long-term protected. Nearly all children (>99.0%) were at least short-term protected, even those that were unvaccinated or whose vaccination status was unknown. Among vaccinated children, participants vaccinated more than 1 or 2 years ago and with a mid-upper arm circumference z-score < -2 were less likely to be long-term protected. Discussion Nearly all adolescents born before the introduction of Hib vaccination in the Lao PDR had antibody titers corresponding to at least short-term protection, indicating a high burden of Hib disease at that time. After vaccine introduction, all but four children (>99%) showed at least short-term protection. Possible explanations for the proportion of protected, yet apparently unvaccinated children, may be past infections, cross-reacting antibodies or faulty vaccination documentation. Our results highlight the need for robust surveillance and reporting of invasive Hib disease to determine the burden of disease despite vaccination.